HUBUNGAN PERUBAHAN FISIK DENGAN KECEMASAN WANITA USIA 40-50 TAHUN DALAM MENGHADAPI MENOPAUSE DI KELURAHAN PAPUSUNGAN KECAMATAN LEMBEH SELATAN - Moudy lombogia (Jurnal Ilmiah Perawat Manado (Juiperdo), 2014)
Women entering menopause usually occurs around the age of 50 years will happen biological changes in the body, particularly the hormone produced by the ovaries. The loss of estrogen and progesterone progressively during menopause increases the risk of women's health and will affect the quality of a woman when his life is supposed to achievesuccess. The purpose of this study is known relationship with anxiety physical changes women aged 40-50 years in the face of menopause in the Village Papusungan Southern District of Lembeh. This study uses the research methods research design is descriptive analytic survey with cross sectional approach. The population in this study were premenopausal mothers, whereas sampled in this study of premenopausal women who meet the inclusion and exclusion criteria as many as 30 respondents, using a sample taking technique is simple random sampling. The instrument used in this study was a questionnaire. Analysis of the data used are univariate and bivariate analysis in which statistical test used is the Spearman rank, using SPSS 16.0. The results are consistent test results obtained statistically significant level of p = 0.966 and r = 0.008 or < r = 0.05 means there is a very strong relationship between the physical changes to the anxiety of women aged 40-50 years in the face of menopause in the Village Papusungan District of South Lembeh